Is Technology Based Note-Taking More Preferable For Millenial Students? Exploration Of English Students' Note-Taking Habit - Murtafi'ah, Muhimatul; Asmiyah, Siti; Fitriah, Fitriah (IJET (Indonesian Journal of English Teaching), 2020)
Note-taking is one of important skills students need to practice in order to understand the content of both printed and unprinted texts effectively. To do note-taking, readers can do either manually or digitally. However, with the advancement of technology nowadays especially in this pandemic era, readers can practice note-taking more easily with the use of technological tools, such as laptop and mobile. This descriptive qualitative research aims to discover how university students practice note-taking particularly to explore their note-taking strategy and preference for refining literature review in English academic writing. This included identifying the strategy they apply in note-taking practices to understand the content of the articles they read and identifying their note-taking. To explore the issue, the researcher collected data through questionnaires and interview with 62 English students taking academic writing who have intense note-taking practices as part of the course activities. The results of this study showed the majority of millennial students prefer using digital note-taking with 66.12% responses. They decided to use it as it is faster and easier in doing note-taking. The digital technology that the students used commonly was mobile phone with 54.84% responses. They chose this tool to practice note-taking as it is handy.